FEATURES OF INTENSIVE NUTRITIONAL SUPPORT OF PREMATURE INFANTS IN INTENSIVE CARE UNIT (PART 1) - K.V. Romanenko; A.P. Averin; A.I. Gaeva; N.Yu. Bogachev (Педиатрическая фармакология)
The article presents the modern approaches to preterm infants feeding, principles of parenteral and enteral nutrition. The importance of adequate control of deficit status in preterm infants at different periods of developmental care is marked. Arguments for using the enriched milk or specialized formulas for prematurity during the in-clinic and out-clinic periods of care are provided.Key words: premature infants, enteral nutrition, formulas for premature infants, breast milk, breast milk enriches.